Contested commons – multiple insecurities of pastoralists in North-Eastern Afghanistan - Kreutzmann, Hermann; Schütte, Stefan (ERDKUNDE, 2011)
Pastoralists in North-Eastern Afghanistan are exposed to a multitude of contemporary challenges and threats while practising mobile animal husbandry in differing locations and within the spheres of varying power constellations. In this article a historical perspective is adopted to explore the challenges and multiple insecurities of Pashtun and Uzbek pastoral communities who seasonally engage in long-distance migration from the lowlands in Northern Afghanistan to the high pastures of Badakhshan. The same pasture area is regularly utilised by Shughni mountain farmers who practise combined mountain agriculture in the high mountain settlements close to Lake Shewa. Debates about nomadism’s place in transforming societies, the drama of the commons, human security, and vulnerability issues frame the discussion of pastoralism in contested commons. Based on empirical evidence derived from open interviews with migrating pastoralists and sedentary groups on the Shewa plateau in Badakhshan, interpretations of pastoralism are presented, embedded in the context of contemporary Afghanistan. Pastoralism as a valuable survival and adaptive strategy is challenged by multiple environmental, social and political insecurities, by militancy and weak state authorities, and it unfolds in contested commons and along dangerous routes. The nexus of legal pluralism, tenure insecurity and changing control of space is identified as an important determining factor for the shape of mobile pastoralism in present-day Afghanistan.